PHYSICAL ACTIVITY, THE ALZHEIMER A PROTECTIVE FACTOR: THE BENEFITS OF THE RELEASE OF BRAIN-DERIVED NEUROTROPHIC FACTOR (BDNF). (Fiep Bulletin - online, 2012)
Alzheimer's disease (AD) is characterized by progressive neuronal loss, which begins at the level of cholinergic structures preferably as the basal ganglia of the brain and is associated with reduced levels of cholinergic enzymes such as acetyl cholinesterase, which is related to the decline of intellectual functions (Perry, 1978). The human body secretes a substance called daily-derived neurotrophic factor that is responsible for activating the hypothalamus (responsible for memory both long and short term). This factor is affected by decreasing the levels of product daily secretion of Alzheimer's. In previous studies (conducted last year) showed that the derived neurotrophic factor is secreted in greater amounts to the execution of exercise, underwent exercise older adults according to their capabilities to test whether or not the increased secretion of factor stopped or decreased neurotrophic effects of Alzheimer's disease. Thus to study a group of 30 elderly people with the disease, underwent routine exercises and measured their memory and Alzheimer's, it was demonstrated that his memory improved considerably.
Keywords: Memory; derived neurotrophic factor; exercise